Identification of Students' Misconceptions on the Photosynthetic and Plant Respiration Concepts Using a Two-Tier Diagnostic Test - Arsyida Yuliasari; Diki Latu Har Hari; Pipit Marianingsih (International Journal of Biology Education Towards Sustainable Development, 2023)
This study aimed to determine the results of analyzing students' misconceptions of photosynthesis and plant respiration using a two-tier diagnostic test instrument in science class XII. Photosynthetic and respiration are considered abstract concepts and difficult for students to understand, allowing misconceptions to occur. A two-tier diagnostic test is one of the diagnostic tests that can be used to identify students' misconceptions. This study used a descriptive qualitative method, using a two-tier diagnostic test and interviews instrument. The sample of the research was 75 students. The result showed that the students' misconceptions of photosynthetic and respiration concepts scored 27.9% in the low category. In comparison, the cause of students' misconception can be the need for students' ability to understand the detail of the teacher's explanation.